PRECISE FEATURES OF RAILROAD ENTERPRISES' LONG-TERM ASSET ORGANIZATION BASED ON INTERNATIONAL STANDARDS - Khurshid Mamasobirovich Misirov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In the article, accounting for long-term assets for the organization of accounting of railway enterprises based on IFRS, bookkeeping accounting, formation of financial statements and fixed assets, attention is focused on aspects of improving the accounting of intangible assets, long-term financial investments.